Analysis of possible markers of effective antitumor cellular immune response before starting therapy with immune check-point inhibitors - A. M. Malkova; R. V. Orlova; N. V. Zhukova; A. R. Gubal; V. V. Sharoiko (Сибирский онкологический журнал)
The aim of the study. to analyse possible markers of an effective antitumor cellular immune response.Material and methods. using the keywords «checkpoint inhibitors, immunotherapy, t-lymphocytes, exhausted t-lymphocytes, anti-tumor immune response», review and original articles (n=34) published from 2005 to 2020 in the Pubmed, Web Of Science, Elsevier databases were selected.Results. the study revealed possible markers reflecting a high activity of an adaptive immune response based on effective recognition of tumor antigens through MHC molecules, a sufficient number of T-lymphocytes and a predominance of T-cytotoxic cells, as well as a low level of expression of inhibitory receptors and small molecules. the presence of single nucleotide polymorphisms in the HLA-I and HLA-II genes encoding MHC-I and MHC-II proteins, respectively, a high level of lymphocytes, among which the most important is the predominance of CD8+ t cells and a low level of T-regulatory cells (T-reg), as well as the presence of single nucleotide polymorphisms in the genes encoding FcγR receptors of T-lymphocytes showed their predictive significance. the diagnostic significance of determining the expression of inhibitory receptors for T-lymphocytes (TIM3, LAG3, TIGIT), especially in combination with the determination of PD-1 expression, was also revealed.Conclusion. the results obtained may be relevant for applying new methods for the assessment of the functional activity of the T-cell immune response before starting therapy with checkpoint inhibitors, as well as for the development of new diagnostic panels, which may be of interest to employees of clinical diagnostic laboratories and research centers.